Design Of A Heating System In A Plastic Injection Molding Machine With A Working Temperature Of 250 C - Dwi Bagas, Achmad Faizal; Muharom, Muharom; Muchid, Mochammad; Nugroho, Alfi; Kholili, Navik (Journal of System Engineering and Technological Innovation, 2023)
The working system of the heating process on a plastic injection molding machine needs to be considered in more detail. Due to the influence of temperature and the type of material according to the quality of the product. In this study, the plastic injection machine that used a temperature variation used several different variations, and three experiments were given at each temperature variation of 200°C – 250°C using 75 grams of plastic material with a heating time of 120-141 seconds and 150 grams of plastic material with a heating time of 120-141 seconds. Warm-up 210-250 seconds. Temperature control using the REX C100 Controller. The injection machine can operate according to the design. Namely, the heating temperature can be adjusted. Implementation and control of the control system show a good response. The plastic to be melted is of the HDPE (High-Density polypropylene) type with a temperature for melting the plastic of 250°C.